Brokers versus Retail Investors: Conflicting Interests and Dominated Products - EGAN, MARK (Journal of Finance, 2019)
ABSTRACT I study how brokers distort household investment decisions. Using a novel convertible bond data set, I find that consumers often purchase dominated bonds—cheap and expensive otherwise‐identical bonds coexist in the market. Brokers are incentivized to sell the dominated bonds, typically earning two times greater fees for selling them. I develop and estimate a broker‐intermediated search model that rationalizes this behavior. The estimates indicate that costly search is a key friction in financial markets, but the effects of search costs are compounded when brokers are incentivized to direct the search of consumers toward high‐fee inferior products.